Pengaruh Manajemen Perubahan, Budaya Organisasi, dan Manajemen SDM terhadap Kinerja Perusahaan pada PT Recapital Asset Management: Pengaruh Manajemen Perubahan, Budaya Organisasi, dan Manajemen SDM terhadap Kinerja Perusahaan pada PT Recapital Asset Management - Dini Andriani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
All organizations face a dynamic and changing environment. The demands of being a competitive organization mean that companies must respond more quickly to customer needs, and this can change over time. It can be said that the external environment of an organization tends to be the force that drives change. On the other hand, organizations internally feel the need for change, thus every organization will face the choice between changing or dying, suppressed by the forces of change. This research aims to determine the effect of change management on company performance, determine the effect of organizational culture on performance, to determine the effect of human resource management on company performance, and together to determine the effect of change management, organizational culture and resource management. Human Resources on Company Performance. This research uses quantitative methods and uses several theories as indicators. This research took data from the population of all PT Recapital Asset Management employees who were the object of the research, by distributing questionnaires. The results of this research show that there is an effect between management changes on company performance which can be determined by management change indicators at 18.4%, while company performance is still determined by other factors at 81.6%. Meanwhile, the strength of the relationship between the two is positive but at a low or weak level. There is an effect between organizational culture on company performance which can be determined by organizational culture indicators at 43.2%, while company performance is still determined by other factors at 56.8%, meanwhile the strength of the relationship between the two is positive but at a moderate level. There is an effect between HR management on company performance which can be determined by HR management indicators at 20.9%, while company performance is still determined by other factors at 79.1%, while the strength of the relationship between the two is positive but at a low or weak level. There is an effect between management changes, organizational culture, HR management together on company performance of 44.3%, while company performance is still determined by other factors at 55.7%. The strength of the relationship between the two is positive but at a moderate level.